Concept and types of legal responsibility of the advocate - Волошина, Л.О (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2016)
The article investigates the theoretical and practical aspects of legal responsibility of the advocate. The author argues that understanding of the nature of the institute of legal responsibility, including legal responsibility of the advocate, traditionally been problematic and controversial. Existing approaches of the legal doctrine for understanding the essence of legal responsibility are thoroughly analyzed. The author definition of legal responsibility of the advocate proposed in this article. The article stipulates that the legal responsibility of the advocate is the relationship arising between a subject who is authorized to apply measures of public-law enforcement and the advocate, who broke the law, which include the possibility of sanctions in case of breach of commitments. Special attention is paid to the different types of legal responsibility of the advocate, such as disciplinary, civil, administrative and criminal responsibility.It is noted that the basis for bringing a lawyer to disciplinary action are committing misconduct, which are: violation of incompatibility; violation of the oath of Advocates of Ukraine; violation of legal ethics; disclosure of confidentiality or actions that led to the disclosure; failure or improper fulfillment of their professional duties; non-enforcement of the legal profession; breach of other obligations lawyer by law.The reason of occurrence of civil liability is unlawful, harmful, and guilty of the act of the person who harmed. In science, the civil rights act of damage can be divided into the following components: a) the unlawful behavior of the person; b) the occurrence of damage) the causal link between the first two elements, d) wine person harmed.Established that the Code of Ukraine on Administrative Offences and the Criminal Code of Ukraine does not contain direct norms on liability lawyer for the crime. The lawyer is criminally responsible as well as other individuals. An example, when recognizing the fact of putting pressure on witnesses, lawyers criminally responsible on general grounds, and its status in no way affects the degree of guilt and punishment

У статті досліджено підходи до розуміння сутності юридичної відповідальності. Розроблено авторське визначення поняття юридичної відповідальності адвоката. Розглянуті види юридичної відповідальності адвоката, зокрема: дисциплінарна, цивільно-правова, адміністративна та кримінальна відповідальність.
ПОНЯТТЯ ТА ВИДИ ЮРИДИЧНОЇ ВІДПОВІДАЛЬНОСТІ АДВОКАТА
Keywords: legal responsibility; attorney (advocate); disciplinary responsibility; civil responsibility; administrative responsibility; criminal responsibility; юридична відповідальність; адвокат; дисциплінарна відповідальність; цивільно-правова відповідальність; адміністративна відповідальність; кримінальна відповідальність